Mapping of Paddy Field Using Geographic Information System in Langsa Timur - joko subali (University of Darussalam Gontor, Ponorogo, East Java Indonesia, 2020)
The existence of standard paddy fields in Eastern Langsa Subdistrict of Langsa continues to experience changes, from paddy fields to non-paddy fields caused by economic growth and increasing population. The purpose of this study was to determine the area of raw paddy fields in East Langsa District and determine the factors that influence changes in the area of raw paddy fields based on Geographic Information Systems (GIS). This research uses on-screen image interpretation techniques combined with field surveys, and uses analytical overlays to find out the conversion of raw paddy fields in 2014 sourced from the Agricultural Extension Agency of East Langsa covering an area of 1,447 hectares and a paddy field area of 2019 results from the interpretation of satellite imagery covering an area of 867.67 Ha, in the last 5 years the conversion of paddy fields was 557.33 Ha (39.90%). If calculated on average, the annual converted paddy fields are 115.46 Ha (7.98%). The factors that cause conversion of paddy fields are four, namely: (1) Demand for land, (2) Conditions of paddy fields, (3) Encouragement to be converted, (4) Distance to the central government of Langsa City, (5) Changing boundaries